Glaucoma detection with matrix and standard achromatic perimetry - Burgansky‐Eliash, Zvia (BMJ Group, 2007)
BACKGROUND: Matrix perimetry is a new iteration of frequency‐doubling technology (FDT) which uses a smaller target size in the standard achromatic perimetry presentation pattern. AIM: To compare the performance of matrix and Swedish interactive thresholding algorithm (SITA) perimetry in detecting glaucoma diagnosed by structural assessment. DESIGN: Prospective cross‐sectional study. METHODS: 76 eyes from 15 healthy subjects and 61 consecutive glaucoma suspects and patients with glaucoma were included. All patients underwent optic nerve head (ONH) photography, SITA and matrix perimetries, and optical coherence tomography (OCT) within a 6‐month period. Glaucoma diagnosis was established by either glaucomatous optic neuropathy or OCT by assessing retinal nerve fibre layer (RNFL) thickness. Mean deviation (MD), pattern standard deviation (PSD), glaucoma hemifield test and cluster of abnormal testing locations were recorded from matrix and SITA perimetries. RESULTS: Similar correlations were observed with matrix and SITA perimetry MD and PSD with either cup‐to‐disc ratio or OCT mean RNFL. The area under the receiver operating characteristic (AROC) curves of MD and PSD for discriminating between healthy and glaucomatous eyes ranged from 0.69 to 0.81 for matrix perimetry and from 0.75 to 0.77 for SITA perimetry. There were no significant differences among any corresponding matrix and SITA perimetry AROCs. CONCLUSIONS: Matrix and SITA perimetries had similar capabilities for distinguishing between healthy and glaucomatous eyes regardless of whether the diagnosis was established by ONH or OCT–RNFL assessment.